Implantation of the clinical-grade human neural stem cell line, CTX0E03, rescues the behavioral and pathological deficits in the quinolinic acid-lesioned rodent model of Huntington's disease. (6th May 2020) - Yoon, Yongwoo; Kim, Hyun Sook; Jeon, Iksoo; Noh, Jeong-Eun; Park, Hyun Jung; Lee, Suji; Park, In-Hyun; Stevanato, Lara; Hicks, Caroline; Corteling, Randolph; Barker, Roger A.; Sinden, John D.; et al.
Abstract: Huntington's disease (HD) is a devastating, autosomal-dominant neurodegenerative disease, for which there are currently no disease-modifying therapies. Clinical trials to replace the damaged striatal medium spiny neurons (MSNs) have been attempted in the past two decades but have met with only limited success. In this study, we investigated whether a clonal, conditionally immortalized neural stem cell line (CTX0E03), which has already shown safety and signals of efficacy in chronic ischemic stroke patients, could rescue deficits seen in an animal model of HD. After CTX0E03 transplantation into the quinolinic acid-lesioned rat model of HD, behavioral changes were measured using the rotarod, stepping, and staircase tests. In vivo differentiation and neuronal connections of the transplanted CTX0E03 cells were evaluated with immunohistochemical staining and retrograde tracing with Fluoro-Gold. We found that transplantation of CTX0E03 gave rise to a significant behavioral improvement compared with the sham- or fibroblast-transplanted group. Transplanted CTX0E03 formed MSNs (DARPP-32) and GABAergic neurons (GABA, GAD65/67) with BDNF expression in the striatum, while cortically transplanted cells formed Tbr1-positive neurons. Using a retrograde label, we also found stable engraftment and connection of the transplanted cells with host brain tissues. CTX0E03 transplantation also reduced glial scar formation and inflammation, as well as increasing endogenous neurogenesis and angiogenesis. Overall, our results demonstrate that CTX0E03, a clinical-grade neural stem cell line, is effective for preclinical test in HD, and, therefore, will be useful for clinical development in the treatment of HD patients. : Abstract : Implantation of the clinical-grade human neural stem cell line, CTX0E03, leads to behavioral improvement, as well as neuronal differentiation and tissue repair in the quinolinic acid-lesioned rodent model of Huntington's disease over the period of 12 weeks following implantation.